Macroeconomics and Monetary Economics - 2: Array - Collective Authors, (Acta Universitatis Danubius. Œconomica, 2021)
The previous paper analized the phenomenon of demographics and poverty for developing countries and regions of the World for developing countries and regions of the World for each of the developing countries or regions of the World. A number of indicators are analyzed, such as: The annual population growth rate, birth rate, crude, life expectancy at birth, the mortality rate, adult, the maternal mortality ratio, people using at least basic sanitation services, the rural poverty gap, the Gini index.